Video-game based exercises for older people with chronic low back pain: a protocol for a feasibility randomised controlled trial (the GAMEBACK trial). Issue 2 (June 2017) - Zadro, Joshua Robert; Shirley, Debra; Simic, Milena; Mousavi, Seyed Javad; Ceprnja, Dragana; Maka, Katherine; Ferreira, Paulo
Abstract: Objectives: To investigate the feasibility of implementing a video-game exercise programme for older people with chronic low back pain (LBP). Design: Single-centred single-blinded randomised controlled trial (RCT). Setting: Physiotherapy outpatient department in a public hospital in Western Sydney, Australia. Participants: We will recruit 60 participants over 55 years old with chronic LBP from the waiting list. Interventions: Participants will be randomised to receive video-game exercise ( n  = 30) or to remain on the waiting list ( n  = 30) for 8 weeks, with follow up at 3 and 6 months. Participants engaging in video-game exercises will be unsupervised and will complete video-game exercise for 60 minutes, 3 times per week. Participants allocated to remain on the waiting list will be encouraged to maintain their usual levels of physical activity. Main outcome measure: The primary outcomes for this feasibility study will be study processes (recruitment and response rates, adherence to and experience with the intervention, and incidence of adverse events) relevant to the future design of a large RCT. Estimates of treatment efficacy (point estimates and 95% confidence intervals) on pain self-efficacy, care seeking, physical activity, fear of movement/re-injury, pain, physical function, disability, falls-efficacy, strength, and walking speed, will be our secondary outcome measures. Results: Recruitment for this trial began in November 2015. Conclusion: This study describes the rationale and processes of a feasibility study investigating a video-game exercise programme for older people with chronic LBP. Results from the feasibility study will inform on the design and sample required for a large multicentre RCT. Trial registration: Australian New Zealand Clinical Trials Registry: ACTRN12615000703505.